Nanotechnology Based Herbal Drug Delivery System: Current Insights and Future Prospects - Chowdhury, Sailee; Nath, Debabrata; Chanda Das, Smriti Rekha; Kar, Koyel; Chakraborty, Priyanka; Kapoor, Devesh U.; Prajapati, Bhupendra G. (Current Nanomedicine, 2024)
Herbal medicines, integral to human history, remain vital in developing countries owing to the high costs of synthetic drugs, with 80% of the population relying on traditional practices. There has been an escalating focus within the scientific community on the exploration of phytoconstituents. This growing interest is due to the diverse benefits offered by herbal or plant-based ingredients. Despite the dominance of allopathic treatments, medicinal plants are still widely used but face challenges like poor absorption and low bioavailability. Many plant-derived pharmacologically active compounds, such as tannins, flavonoids, and terpenoids, show poor solubility in water. This low solubility, amalgamated with their inability to efficiently cross lipid-cell membranes due to their large molecular size, considerably hinders their absorption. These factors lead to declined efficacy and lower bioavailability of these compounds. Nanotechnology enhances the effectiveness of medicinal plants through strategies such as polymeric nanoparticles (NPs), solid lipid nanoparticles (SLNPs) and liposomes, improving solubility, protection and controlled release. These advances revolutionize drug delivery, surging the bioavailability and therapeutic value of herbal formulations. Nanomedicine employs NPs and nanorobots for enhanced bioavailability, solubility and targeted delivery, despite challenges like understanding working principles, potential toxicity and production scalability. Innovations in biopolymer-based systems, including chitosan and alginate NPs and advanced delivery systems like dendrimers and inorganic NPs, show significant potential. NPs have been effectively utilized to improve the pharmacokinetic and pharmacodynamic properties of various drugs. By integrating biotechnological systems and phytosomes, the bioavailability and bioactivity of herbal drug formulations can be significantly enhanced. The future of nanomedicine is promising, with ongoing research enhancing therapy precision and effectiveness and reducing adverse effects, making continued exploration in this field highly worthwhile.
Keywords: nanotechnology